Imiquimod liposome gel preparations and their ability to inhibit hypertrophic scars - Yujian LIN; Xi LUO; Yanshan ZHAN; Ruiping LIU; Xiaoqi XU; Jun SHI (Journal of Holistic Integrative Pharmacy)
[Abstract]: Objective: This study evaluates the efficacy of imiquimod liposome gel (IMQ-Lips gel) to prevent and treat hypertrophic scars (HS). Methods: On the basis of an orthogonal L9 (34) design, IMQ-Lips formulations were optimized using the film dispersion-pH gradient method. The optimal parameters were phospholipid–cholesterol (3 : 1), lipid-to-drug ratio (8 : 1), and a vitamin E of 5 mg. The in vitro transdermal experiment and rabbit HS model were used to evaluate the pharmacodynamics in vitro and in vivo. Results: IMQ-Lips has good physical and chemical properties, with an encapsulation rate of 81.2% ± 1.9%, an average diameter of (347 ± 21) nm, and a zeta potential of (–12.19 ± 1.7) mV. In vitro transdermal penetration tests showed that IMQ-Lips gel enhanced skin retention and reduced transdermal delivery compared with IMQ gel. The rabbit HS model further revealed that IMQ-Lips gel treatment reduced scar formation by inhibiting overproliferation of fibroblasts and reducing interleukin-4 levels. Conclusion: Taken together, these data suggest that IMQ-Lips gel represents a potential therapeutic approach for HS treatment.